Factors aﬀecting eating habits and knowledge of edible ﬂowers in diﬀerent countries. - Guiné, Raquel P. F. (2021)
The use of edible flowers (EF) in gastronomy is gaining popularity; however, there is still a lack of information about the factors that most contribute to the acceptance of this product. Therefore, the objective of this study was to investigate the habits associated with the usage of edible flowers in gastronomy in three different countries (Portugal, Slovenia and Brazil) and also to evaluate the major determinants for those habits. Additionally, the level of knowledge was also investigated, particularly in regards with aspects such as perceived risks of toxicity and pesticides. For that, it was used a questionnaire survey of self-response carried out on a sample of 559 participants, form the above mentioned countries. To analyse the data basic descriptive statistical tools were used combined with crosstabs and chi-square tests. Finally a tree classification was performed using the CRT (Classification and Regression Trees) algorithm. The results revealed that, regardless of the country, the participants were familiar with the use of edible flowers in gastronomy. The participants had, in general, already consumed EF and their use was more popular between the Portuguese participants, being the Brazilian those who used them less. There were found significant differences between countries in the form of consumption of edible flowers and also in the types of edible flowers consumed. There were also significant differences regarding the reasons for eating edible flowers. The classification analysis showed that the country and the level of education were the major determinants for the consuming habits and knowledge about EF. This study highlighted that eating habits are very dependent on the customs and traditions of each country and helped understanding the factors that most affect the participants’ attitudes towards the consumption and knowledge of edible flowers.